Design of Hybrid Polymer Nanofiber/Collagen Patches Releasing IGF and HGF to Promote Cardiac Regeneration - Eloise Kerignard; Audrey Bethry; Chloé Falcoz; Benjamin Nottelet; Coline Pinese (MDPI AG, 2022)
Cardiovascular diseases are the leading cause of death globally. Myocardial infarction in particular leads to a high rate of mortality, and in the case of survival, to a loss of myocardial functionality due to post-infarction necrosis. This functionality can be restored by cell therapy or biomaterial implantation, and the need for a rapid regeneration has led to the development of bioactive patches, in particular through the incorporation of growth factors (GF). In this work, we designed hybrid patches composed of polymer nanofibers loaded with HGF and IGF and associated with a collagen membrane. Among the different copolymers studied, the polymers and their porogens PLA-Pluronic-PLA + PEG and PCL + Pluronic were selected to encapsulate HGF and IGF. While 89 and 92% of IGF were released in 2 days, HGF was released up to 58% and 50% in 35 days from PLA-Pluronic-PLA + PEG and PCL + Pluronic nanofibers, respectively. We also compared two ways of association for the loaded nanofibers and the collagen membrane, namely a direct deposition of the nanofibers on a moisturized collagen membrane (wet association), or entrapment between collagen layers (sandwich association). The interfacial cohesion and the degradation properties of the patches were evaluated. We also show that the sandwich association decreases the burst release of HGF while increasing the release efficiency. Finally, we show that the patches are cytocompatible and that the presence of collagen and IGF promotes the proliferation of C2C12 myoblast cells for 11 days. Taken together, these results show that these hybrid patches are of interest for cardiac muscle regeneration.